How to Manage Lung Injury Related to Cancer Therapy? - Haryati, Haryati; Saputra, Muhammad Hendi; Wati, Farah Fatma (Jurnal Respirasi, 2025)
Modern technology has improved our understanding of cancer biology, especially anti-cancer medicines from cytotoxic chemotherapy, radiotherapy, targeted therapy, and immunotherapy. Nevertheless, these treatments can result in significant pulmonary toxicities, including interstitial lung disease (ILD) and radiation-induced lung injury (RILI), which can result in a high rate of morbidity and mortality despite being less severe than injuries to other organ systems. Lung injury mechanisms occur through various pathways, such as immune-mediated damage and oxidative stress. Through clinical history and examination, imaging techniques such as high-resolution computed tomography (HRCT), and the necessity of eliminating other possibilities of respiratory symptoms, lung injuries due to cancer therapies can be identified. The management strategies are based on the severity of the condition and may include discontinuing the responsible agent, corticosteroid treatment, and supportive care. The challenge is early identification and management of these lung injuries due to the variability in patient responses and the lack of comprehensive guidelines. Therefore, awareness is needed to monitor lung health in cancer patients undergoing therapy.